Resíduos de bambu (Bambusa vulgaris Schrad.) para a produção de carvão ativado - Santana, Gregório Mateus (2014)
Bamboo waste (Bambusa vulgaris Schrad.) were used as a precursor material in the production of various types of activated carbon (ACs). For the ACs production two types of activations were applied: 1) physical activation with carbon dioxide (CO 2 ) and water vapor (H 2 O); and 2) chemical activation with a salt (zinc chloride - ZnCl 2 ), an acid (phosphoric acid - H 3 PO 4 ) and a base (sodium hydroxide - NaOH). The ACs obtained were characterized by elemental analysis (CHNS), scanning electron microscopy (SEM), Boehm titration method (BOEHM) and surface area per methylene blue (S AM ). The materials were tested for their ability to adsorb methylene blue, phenol and ion Cr +6 . All ACs obtained showed high yield. By elemental analysis, it was found, increased of carbon levels and decrease of oxygen levels and hydrogen. The ACs morphology are different between them and varied according to the impregnation type used, the precursor material, charcoal and commercial AC. By the Boehm titration method, it was noted that materials activated physically have a lower total acidity than chemically activated and chemical activation increased the amount of carboxylic groups. The AC ZnCl 2 and AC H 2 O were the most efficient in the adsorption of methylene blue. The AC ZnCl 2 , AC CO 2 , AC H 2 O and AC H 3 PO 4 were the best adsorbent for phenol, while only the AC ZnCl 2 , AC H 3 PO 4 and AC commercial adsorbed the hexavalent chromium. The AC ZnCl 2 was the only one that exhibited the largest surface area (1319.16 m 2 .g -1 ). The ACs showed results equal or higher than the commercial AC.